Black Spot of Rose - Jozer Mangandi; Natalia A. Peres (EDIS, 2009)
PP268, a 5-page illustrated fact sheet by Jozer Mangandi and Natalia A. Peres, describes this fungal disease that that affects nearly all rose cultivars worldwide — causal agent and geographic distribution, symptoms, and control. Published by the UF Department of Plant Pathology, May 2009.